Consumption Pattern Of Nutrition And Infection Disease Relating To The Chronic Energy Deficiency On Pregnant Woman In Working Region Puskesmas Selat Karangasem District - Ni Putu Dian Ardianti; I Made Rodja Suantara; I Komang Agusjaya (Jurusan Gizi, Poltekkes Kemenkes Denpasar dan DPD PERSAGI Bali, 2018)
In Indonesia based on data from Riskesdas (Ministry of Health, 2013) the prevalence of the risk of chronic energy deficiency (CED) in pregnant women (15 - 49 years) was 24.2%. The purpose of this study was to determine the pattern of consumption of nutrients and infectious diseases in relation to the incidence of chronic energy deficiency in pregnant women conducted for 4 months, 2018 in the working area of the Puskesmas Selat, Karangasem regency. The design of this research is cross sectional. The research sample of all pregnant women who examined their pregnancies at the Puskesmas Selat was 53 samples. The data collected are CED data, consumption patterns (different types of food ingredients, the amount of energy and protein consumption and frequency of eating), infectious diseases (environmental sanitation and personal hygiene). Furthermore, the data is analyzed descriptively using frequency tables and cross tables. The results of this study found the prevalence of KEK pregnant women 18.9% and normal pregnant women 81.1%. The average energy consumption was 1989.4 kcal (SD 333.5), the result of energy consumption was 54.7% moderate, 28.3% less and 17.0% deficit. The average protein consumption is 66.3 grams (SD 10.1), the results of protein consumption are 54.7% medium and 45.3% deficit. Data on infectious diseases 15.1% have suffered from infectious diseases and 84.9% have never suffered from infectious diseases. Environmental sanitation of CED pregnant women is 80.0% good and normal pregnant women are 90.0% good. Personal hygiene pregnant women with CED 80.0% are good and normal pregnant women are 97.7% good. The tendency of low energy and protein consumption will increase the incidence of CED. Therefore it is needed nutrition counseling and counseling about balanced nutrition, danger of KEK for the mother and fetus they contain, cross-sectoral and cross-program involvement to reduce the prevalence of CED.Keywords : Chonic Energy Deficiency (CED), consumption patterns, infectious diseases and pregnant women